2016
DOI: 10.1111/gtc.12356
|View full text |Cite
|
Sign up to set email alerts
|

Conserved interaction of Ctf18‐RFC with DNA polymerase ε is critical for maintenance of genome stability in Saccharomyces cerevisiae

Abstract: Human Ctf18-RFC, a PCNA loader complex, interacts with DNA polymerase ε (Polε) through a structure formed by the Ctf18, Dcc1, and Ctf8 subunits. The C-terminal stretch of Ctf18, which is highly conserved from yeast to human, is necessary to form the Polε-capturing structure. We found that in the budding yeast Saccharomyces cerevisiae, Ctf18, Dcc1, and Ctf8 formed the same structure through the conserved C terminus and interacted specifically with Polε. Thus, the specific interaction of Ctf18-RFC with Polε is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…Recent studies have also shown that RFC Ctf18 is able to bind to DNA polymerase epsilon (Pol e) via the catalytic subunit Pol2 [57,60,61]. This interaction requires the intact Ctf18 C -Ctf8-Dcc1 complex which we present in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Recent studies have also shown that RFC Ctf18 is able to bind to DNA polymerase epsilon (Pol e) via the catalytic subunit Pol2 [57,60,61]. This interaction requires the intact Ctf18 C -Ctf8-Dcc1 complex which we present in this study.…”
Section: Discussionsupporting
confidence: 60%
“…This suggests that ctf18-RAA dcc1WH3Δ/pol2-5A mutants load sufficient PCNA to support cohesion establishment. Whether this is mediated by recruitment of the mutant Ctf18-RFC near forks via alternative interactions or by some residual and transient binding to Pol2, which can only be removed by complete disruption of the Ctf18-1-8 module (Okimoto et al ., 2016), is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…The Ctf18-1-8 module comprises a triple-barrel domain (TBD) formed from all three proteins and a winged helix hook (WHH), composed of a series of winged-helix domains in the C-terminus of Dcc1 resembling a hook (Grabarczyk, Silkenat and Kisker, 2018; Wade et al ., 2017). Mutations in Ctf18 that disrupt formation of this Ctf18-1-8 module result in similar but not identical phenotypes as entire deletions of Ctf18 (Okimoto et al ., 2016; García-Rodríguez et al ., 2015), suggesting that this module is critical for at least some of the specialized functions of Ctf18-RFC. It has been shown that the Ctf18-1-8 module binds the N-terminal catalytic domain of Pol2 (García-Rodríguez et al ., 2015; Murakami et al ., 2010), the largest subunit of the leading strand Pol ε, and that this interaction increases the clamp loader activity of Ctf18-RFC (Fujisawa et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Eco1 associates with PCNA and promotes cohesion by acetylating the cohesion subunit Smc3 during S phase [ 84 , 85 , 86 , 87 ]. The fact that loss of either Ctf18, Dcc1, or Ctf8 causes cohesion defects and that these molecules form a DNA polymerase ε binding module suggest that sufficient levels of PCNA on the leading strand must be supplied by Ctf18-RFC, which would support polymerase ε and Eco1 acetylation activity [ 55 , 88 , 89 ].…”
Section: The Three Rfc Complexes Contribute To Genomic Integrity Bmentioning
confidence: 99%